SOYBEAN VARIETIES FOR ALTAY AREA AND THEIR CULTIVATION FEATURES - E. R. Shchukis; S. K. Shchukis (Зерновое хозяйство России, 2018)
There is a great necessity of a set of highly productive, well-adapted, complementary, economically specific and ecologically differentiated crops and varieties to realize agro climatic potential of West Siberia. Soybean is one of them. The volume of soybean production is constantly increasing worldwide. The sowing areas of the crop exceeded 100 ml hectare and continue increasing. During the last years soybean areas in Russia were increased fiftyfold, but the pace of soybean development significantly lags behind the leading countries of the world.The share of soybean is only one per cent of all worldwide sowings. The sowing areas in Altay Area vary from 10 till 23 thousand of hectare, being 18838 ha in 2014. The paper emphasizes the importance of soybean as a food and fodder crop. It considers the possibilities of its implementation in the conditions of Pre-Ob forest steppe of Altay, the ways of its productivity increase. The paper gives the analysis of varieties, discusses methods, principles and ways of improvement of soybean varieties and total characteristics of the new variety ‘Nadezhda’.